227k views
1 vote
Add (5y - 1)+ (-2y + 4)​

User Ptim
by
4.5k points

2 Answers

5 votes

Answer:

3y+3

Explanation:

"Simplifying

(5y + -1) + (-2y + 4) = 0

Reorder the terms:

(-1 + 5y) + (-2y + 4) = 0

Remove parenthesis around (-1 + 5y)

-1 + 5y + (-2y + 4) = 0

Reorder the terms:

-1 + 5y + (4 + -2y) = 0

Remove parenthesis around (4 + -2y)

-1 + 5y + 4 + -2y = 0

Reorder the terms:

-1 + 4 + 5y + -2y = 0

Combine like terms: -1 + 4 = 3

3 + 5y + -2y = 0

Combine like terms: 5y + -2y = 3y

3 + 3y = 0

Solving

3 + 3y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.

3 + -3 + 3y = 0 + -3

Combine like terms: 3 + -3 = 0

0 + 3y = 0 + -3

3y = 0 + -3

Combine like terms: 0 + -3 = -3

3y = -3

Divide each side by '3'.

y = -1

Simplifying

y = -1 "

User Nube
by
4.6k points
3 votes

Answer:

3y + 3

Explanation:

(5y - 1) + (-2y + 4) =

3y + 3

User Neil Slater
by
4.6k points